1990
DOI: 10.1016/0266-7681(90)90013-t
|View full text |Cite
|
Sign up to set email alerts
|

Is the treatment of enchondroma in the hand by simple curettage a rewarding method?

Abstract: 46 enchondromata of the hand have been treated by simple curettage without bone grafting. 82% healed and 16% were left with only small bone defects. Only one patient had a clear-cut recurrence requiring re-operation. This simple method, performed on out-patient basis, is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0
7

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 12 publications
0
44
0
7
Order By: Relevance
“…It is well-known that a fresh fracture is surrounded by hematoma, and this hematoma will be invaded by multipotent mesenchymal cells which diVerentiate into osteoblasts, a pre-requisite for bone healing [7]. Therfeore, curettage has recently become the mainstay of surgical treatment for enchondroma.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that a fresh fracture is surrounded by hematoma, and this hematoma will be invaded by multipotent mesenchymal cells which diVerentiate into osteoblasts, a pre-requisite for bone healing [7]. Therfeore, curettage has recently become the mainstay of surgical treatment for enchondroma.…”
Section: Discussionmentioning
confidence: 99%
“…In cases of solitary enchondroma, some authors have recommended simple curettage without bone grafting and have reported good clinical results, especially in younger patients. However, such patients must undergo casting and wait for 4 to 6 weeks before they can resume unrestricted daily activity, and some patients experience joint contracture of the affected limb [7,16,17]. Autologous bone grafting is performed conventionally, but the contribution of cancellous bone to the structural strength in the short term is considered to be very low [9].…”
Section: Discussionmentioning
confidence: 99%
“…This is a well accepted method of repair because patients treated with curettage alone will form new bone to fill in the surgical cavity (7,8). It has been hypothesized that the hematoma at the fracture site becomes invaded by mesenchymal multipotent cells which can differentiate into osteoblasts providing the cellular network for bone growth (8).…”
Section: Discussionmentioning
confidence: 99%